KAJIAN PEDAGOGIS KISAH NABI IBRAHIM DALAM SURAT MARYAM AYAT 42-48 - Ismail Anshari (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
The challenges faced by the Prophets, in the form of physical intimidation to mental intimidation, did not only come from their followers and even from their own families. Library Research research was carried out with a qualitative approach, which aims to obtain input in the development of a curriculum that is relevant to the development of human life in their respective times. The results of this study conclude that Prophet Ibrahim used a very simple, yet very decisive method. Namely the dialogical persuasion method, with very communicative and diplomatic word choices. However, in the end, history determined differently that it turned out that the Prophet's own families did not guarantee that someone would easily be given guidance by God.